Aplicación de los métodos GUM y Monte Carlo para el análisis de la confiabilidad metrológica en equipos industriales: estudio de caso de los procesos térmicos en un motor de combustión interna (2022)
This Project is aligned to the research project No 2022008 that is approved by the Vice President for Science, Technology and Innovation of the Antonio Nariño University, which is entitled: "Development of statistical techniques for the analysis of uncertainty and metrological performance in industrial equipment". Although the projects seek similar objectives, while the project approved by the VCTI focuses on industrial equipment for hydroelectric power generators in a hydroelectric plant in Rio de Janeiro (Brazil), this degree project applies the methodology proposed for another industrial equipment, that is, an internal combustion engine. Thus, this project arises with the alternative solution to the problem that affects the efficiency in the process and production in industrial plants or in any other area where there are associated temperature measurements. This is due to the fact that there is no exact reading of the constant temperature in the measurand. It was important to carry out this research since it focuses on the comparison study between the Monte Carlo method and the GUM method, in terms of the metrological reliability of industrial processes, that is, in the analysis of measurement uncertainty. To achieve the objectives pursued, sensors were used to measure the temperature of an internal combustion engine, as well as a scale to measure fuel consumption. The results allowed verifying the applicability of both methods in search of the continuous improvement of thermal processes at an industrial level.